CURRENT STATE OF INVASIVE ASCLEPIAS SYRIACA IN ROMANIA: MORPHOLOGICAL AND ANATOMICAL INSIGHTS (Acta Horti Botanici Bucurestiensis, 2024)
Numerous ornamental plant species introduced to Europe have become invasive. Asclepias syriaca L. is a notable example and the focal point of our research. Na tive to North America, it was introduced to Europe in 1629 and is currently listed as an invasive species of concern under EU Regulation 1143/2014. In Romania, the species was first reported in 1836. Asclepias syriaca  demonstrates a high capacity to adapt to various climatic and edaphic conditions. In Europe, it primarily inhabits abandoned agricultural lands, wet and dry meadows, road edges, and tree plantations, negatively impacting agriculture. The species exhibits competitive traits such as height, shad e tolerance, vegetative propagation, drought resistance, and allelopathic potential. The aim of this study was to investigate the ecological and anatomical characteristics contributing to the invasive potential of Asclepias syriaca in Romania. The analyses of the current state of the species’ populations highlighted the environmental conditions that support its establishment and spread. Additionally, anatomical investigations revealed structural traits that further emphasize its adaptability to diverse envi ronmental conditions. This study enhances our understanding of the ecology and adaptive capacity of Asclepias syriaca , with significant implications for managing ecosystems affected by this invasive species in Romania.
Keywords: alien plants; anatomy; ornamental plants; structural adaptations